Understanding the startup's intention of digital marketing's learners: An application of the theory of planned behavior (TPB) and technology acceptance method (TAM) - Pham Thi Phuong Dung; Ho Minh An; Pham Quoc Huy; Nguyen Le Dinh Quy (Cogent Business & Management, 2023)
Due to its low entry barrier, minimal overhead, and high return on investment, digital marketing has become more popular among startups, small and medium-sized enterprises as well as all businesses. There is a high need for workers skilled in Digital Marketing, so it is no surprise that schools are vying for students with an interest in this area. In this study, we will look at how students of digital marketing feel about the goals of startups, using data from recent studies to help us draw conclusions. The findings indicate that there is a strong positive relationship between startups' propensity to use digital marketing tools and their intended behavior, which has a positive effect on their intention to launch a business. The results also support the theoretical hypotheses of the Technology Acceptance Model (TAM), as entrepreneurs' propensity to use digital marketing tools has a direct impact on their intention to launch a business. Consistent with recent research, these findings indicate that the level of adoption of technological innovations can predict people's intent to act in particular ways. This study offers insights for entrepreneurs and policymakers seeking to promote entrepreneurship by maximizing the potential of digital marketing tools.Based on theory of planned behavior (TPB) and the technology acceptance model (TAM), this research has also helped bring to light the role of normative influence and behavioral control in shaping entrepreneurs' intention.
Keywords: 650; Digital marketing; theory of planned behavior; technology acceptance model; startup